PTEN Controls the DNA Replication Process through MCM2 in Response to Replicative Stress - Jiawen Feng; Jing Liang; Jiaju Li; Yunqiao Li; Hui Liang; Xuyang Zhao; Michael A. McNutt; Yuxin Yin (Cell Reports, 2015)
PTEN is a tumor suppressor frequently mutated in human cancers. PTEN inhibits the phosphatidylinositol 3-kinase (PI3K)-AKT cascade, and nuclear PTEN guards the genome by multiple mechanisms. Here, we report that PTEN physically associates with the minichromosome maintenance complex component 2 (MCM2), which is essential for DNA replication. Specifically, PTEN dephosphorylates MCM2 at serine 41 (S41) and restricts replication fork progression under replicative stress. PTEN disruption results in unrestrained fork progression upon replication stalling, which is similar to the phenotype of cells expressing the phosphomimic MCM2 mutant S41D. Moreover, PTEN is necessary for prevention of chromosomal aberrations under replication stress. This study demonstrates that PTEN regulates DNA replication through MCM2 and loss of PTEN function leads to replication defects and genomic instability. We propose that PTEN plays a critical role in maintaining genetic stability through a replication-specific mechanism, and this is a crucial facet of PTEN tumor suppressor activity.